A method for preparing super-hydrophobic anti-freezing coating material by using waste wind power blades
Patent Information
- Application Number
- CN202411694553.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-11-25
AI Technical Summary
但在该专利申请的技术方案中,关于废弃风电叶片的再利用高价值赋能方面仍为空白
[0040](1)本发明提供了一种利用废弃风电叶片制备超疏水防冻涂料的方法,基于工业用磨盘形固相力化学反应器碾磨废弃风电叶片材料所得具有特殊性能的风电叶片粉体,经对比实验发现,经工业用磨盘形固相力化学反应器碾磨后的粉体,相较于其它粉碎/破碎方式所得粉体,在类似粒径条件下,其疏水性能具有显著的提升,利用其制备涂料所形成的涂层具有粗糙表面和多尺度结构,且这一结构特性与后续疏水改性结合提高了疏水性,实现了改性效果的高效表达。
Smart Images

Figure CN119490792B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-value reuse of waste / retired wind turbine blade materials and hydrophobic coating technology. Specifically, it relates to a method for preparing superhydrophobic antifreeze coatings using waste wind turbine blades, and particularly to the treatment of the aforementioned waste wind turbine blade materials using an industrial disc-shaped solid-phase chemical reactor disclosed in Chinese invention patent CN114534660B. Background Technology
[0002] With increasing global demand for renewable energy, wind power is increasingly becoming part of the global energy landscape due to its sustainability and continuous availability. However, a wave of wind turbine (WT) blade retirements is imminent, with the replacement of obsolete wind turbine components and the expiration of the lifespan of installed equipment (typically 20 to 25 years), leading to significant challenges related to the management of composite waste. WT blades are primarily composed of glass fiber or carbon fiber reinforced epoxy resin (GFRP / CFRP), and the three-dimensional cross-linked network of waste epoxy resin makes it difficult to reshape and dissolve, posing a significant challenge to recycling. In fact, epoxy recycling is generally considered infeasible. Current estimates indicate that approximately 2 million tons of wind turbine blades will be generated annually, and it is projected that by 2050, 43 million tons of wind turbine blades will be discarded globally, causing serious environmental problems. Currently, the main methods for large-scale management of waste wind turbine blades still focus on incineration and landfill, both of which severely pollute the environment and waste valuable resources. At the same time, the unsustainability of these methods conflicts with the principles of a circular economy and carbon neutrality. Therefore, there is an urgent need to develop innovative recycling models for WT blades that reduce environmental impact and promote resource reuse. To address these challenges, several new recycling methods have been proposed in recent years to tackle the recycling challenges of thermoset composites in sustainable energy infrastructure. These methods include mechanical recycling technologies (e.g., grinding, crushing, and pulverizing), chemical processes (e.g., hydrolysis, glycolysis, and dissolution), and thermal treatments (e.g., pyrolysis, thermal decomposition, and fluidization processes).
[0003] However, these methods have serious limitations; for example, pyrolysis requires very high levels of infrastructure, energy consumption, and cost. Therefore, achieving green, efficient, and value-added recycling of epoxy thermosetting composites remains a challenge from an environmental and resource utilization perspective. Among these recycling methods, mechanical recycling is considered an efficient method with large-scale applications; however, this method causes glass fiber breakage and a reduction in aspect ratio. Currently, mechanically recycled WT blade waste is typically used as low-value-added fillers, such as in construction materials, concrete fillers, and bulk molding compounds.
[0004] To provide a new approach for the recycling of waste wind turbine blades, the inventors' prior patent application, "Glass Reinforced Plastic (GRP) Products Using Waste Wind Turbine Blades as Raw Materials and Their Preparation Method" (CN118063854A), provides a method for preparing highly compatible and reactive fillers using waste wind turbine blades. The method involves pre-treating the waste wind turbine blade products and then grinding them in a disc-shaped solid-state mechanical chemical reactor to obtain ultrafine wind turbine blade powder. This ultrafine powder is then mixed with an activator and co-ground to obtain a highly compatible and reactive filler. Finally, this highly compatible and reactive filler is used as a partial raw material to prepare recycled GRP products.
[0005] While the aforementioned patent application provides a new basic approach to the recycling of waste wind turbine blades, and the highly compatible and reactive filler prepared therefrom can be successfully added to resin-based materials as a partial raw material, thus possessing basic reinforcing functionality, it still falls short in terms of high-value-added reuse of waste wind turbine blades. Summary of the Invention
[0006] To address the problems in the prior art, this invention provides a method for preparing superhydrophobic antifreeze coatings using waste wind turbine blades. The method utilizes wind turbine blade powder with special properties obtained by grinding waste wind turbine blade materials in an industrial disc-shaped solid-state chemical reactor. After modification, a high-performance superhydrophobic antifreeze coating is prepared. The coating formed by applying this material exhibits a hierarchical structure and low surface free energy, as well as excellent mechanical properties, durability, chemical stability, and anti-icing properties, thus expanding high-value application scenarios for the reuse of waste wind turbine blade materials.
[0007] To achieve the above objectives, the present invention employs a technical solution consisting of the following technical measures.
[0008] In one aspect, the present invention provides a method for preparing superhydrophobic antifreeze coatings using discarded wind turbine blades, mainly comprising the following steps:
[0009] (1) After the waste wind turbine blade material has undergone pretreatment including washing, it is processed and crushed into wind turbine blade fragments with an average particle size of no more than 3 cm.
[0010] (2) The wind turbine blade fragments obtained in step (1) are added to a grinding disc-shaped solid-state chemical reactor for grinding and crushing. After grinding is completed, the wind turbine blade powder is collected. The process parameters of the grinding disc-shaped solid-state chemical reactor are: grinding pressure of 4-6 MPa, grinding disc surface temperature of 20-30℃ by introducing circulating cooling liquid, grinding at least once, and grinding disc speed of 20-40 rpm.
[0011] (3) The wind turbine blade powder obtained in step (2) is modified by a silane coupling agent containing thiol to prepare thiol-functionalized wind turbine blade powder.
[0012] (4) The thiol-functionalized modified wind turbine blade powder obtained in step (3) is reacted with fluorinated acrylate through a thiol-olefin click chemical reaction to generate a superhydrophobic antifreeze composite powder.
[0013] The fluorinated acrylate has at least one fluorine atom and a carbon chain length of 4 to 20.
[0014] (5) Using the superhydrophobic antifreeze composite powder obtained in step (4) as a raw material, mix it evenly with the other raw materials listed below to prepare a superhydrophobic antifreeze coating:
[0015] 3-5 parts of superhydrophobic antifreeze composite powder
[0016] Solvent 90-95 parts.
[0017] In this article, step (1) includes a pretreatment of washing, which mainly removes impurities from the surface of the waste wind turbine blade material. If necessary, the non-wind turbine blade material should also be removed. Those skilled in the art can carry out specific treatment according to the actual condition of the waste wind turbine blade products that they need to recycle, based on existing technologies.
[0018] In this article, the wind turbine blade fragments processed and crushed to a uniform particle size of no more than 3 cm in step (1) can be processed and crushed using conventional crushing methods, such as jaw crushers, planetary ball mills, cryogenic ball mills, and other existing conventional crushing equipment, in order to facilitate their placement into a disc-shaped solid-phase mechanical chemical reactor for grinding.
[0019] The millstone-shaped solid-phase mechanochemical reactor mentioned in step (2) is the industrial millstone-shaped solid-phase mechanochemical reactor disclosed in Chinese invention patent CN114534660B.
[0020] It should be noted that this industrial millstone-shaped solid-phase mechanochemical reactor is an industrial device that is an improvement on the mechanochemical reactor disclosed in the prior authorized patent ZL95111258.9. It is significantly different from the structure of the laboratory prototype machine when ZL95111258.9 was applied for. It has designed a brand-new millstone structure for industrial high-efficiency mechanochemical grinding, which has been improved from the previous vertical millstone setting to a horizontal setting, and the size of the millstone has been greatly increased. Based on the horizontal setting and large size of the millstone, related fixed millstone components and hydraulic lifting system have been innovatively designed, which greatly improves its three-dimensional shear force, thereby achieving industrial mass production efficiency.
[0021] Typically, the grinding process is at least once. When the grinding process is twice or more, the actual operation involves grinding the material in a disc-shaped solid-state chemical reactor, collecting the product at the discharge end, and then placing it back into the disc-shaped solid-state chemical reactor for grinding. This process is considered as two grinding cycles.
[0022] In this article, the grinding disc surface temperature in step (2) is controlled to be 20-30°C by introducing a circulating cooling liquid, which is water, ethylene glycol or glycerin.
[0023] In this document, the thiol-containing silane coupling agent mentioned in step (3) is a commercially available silane coupling agent with a thiol functional group that is commonly used in the prior art, such as any one or more of KH590 and KH580.
[0024] In this paper, the wind turbine blade powder described in step (3) is modified with a thiol-containing silane coupling agent to obtain thiol-functionalized wind turbine blade powder. Modifying the material using a thiol-containing silane coupling agent is a conventional modification method in the art. Specific modification conditions and operations can be found in the instructions for use of the selected silane coupling agent or in existing technical literature. Typically, in this modification process, the thiol-containing silane coupling agent is diluted to a coupling agent solution with a mass concentration of 1–3 wt%, and then added to the wind turbine blade powder for reaction; or the wind turbine blade powder is fully diluted and dispersed in a mixture A with a mass concentration of 1–3 wt%, and then the thiol-containing silane coupling agent is added for reaction. The dilution and the solvent used for dilution are conventional and well-known methods for using silane coupling agents. Those skilled in the art can directly select a suitable method based on common knowledge in the art or the instructions for use of the thiol-containing silane coupling agent.
[0025] To better illustrate the present invention and provide a technical solution for reference, the wind turbine blade powder described in step (3) is modified with a thiol-containing silane coupling agent to obtain thiol-functionalized wind turbine blade powder. The specific method is as follows:
[0026] By mass, 1-2 parts of wind turbine blade powder are added to 90-99 parts of ethanol and 1-3 parts of deionized water, and the mixture is continuously stirred for 30-40 minutes to disperse it. Then, 1-5 parts of silane coupling agent containing mercapto groups are added, and the mixture is stirred and reacted at a temperature of 90-100℃ for 8-16 hours. After the time is up, the mixture is filtered, washed, and dried to obtain mercapto-functionalized modified wind turbine blade powder.
[0027] In one technical solution, the fluorinated acrylate in step (4) is selected from 1H,1H,2H,2H-perfluorodecyl acrylate, trifluoroethyl acrylate, N-ethylperfluorooctylsulfonamide ethyl acrylate, 1,1,2,2-tetrahydroperfluorohexyl methacrylate, 1,1,2,2-tetrahydroperfluorodecyl methacrylate, 1,1,2,2-tetrahydroperfluorooctyl methacrylate, 1,1,2,2-tetrahydroperfluorododecyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 3-( The following are all of the following: perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 1H,1H,2H,2H-perfluorooctyl acrylate, 1,1,2,2-tetrahydroperfluorotetradecyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, perfluoroalkyl ethyl methacrylate, perfluoroalkyl ethyl acrylate, nonafluorohexadecyl acrylate, (2H-perfluoropropyl)-2-acrylate, and (perfluorocyclohexyl) methacrylate.
[0028] In this paper, the thiol-functionalized modified wind turbine blade powder and fluorinated acrylate in step (4) are reacted with thiol-olefin click chemistry to generate superhydrophobic antifreeze composite powder. Those skilled in the art can know the reaction conditions and process operation of thiol (thiol-olefin click chemistry) reaction based on the common knowledge of chemical synthesis in the art, according to the selection of thiol-functionalized modified wind turbine blade powder and fluorinated acrylate provided by this invention. For example, the initiator, solvent and target product used can all refer to conventional thiol (thiol-olefin click chemistry) reaction.
[0029] To better illustrate the present invention and provide a technical solution for reference, the superhydrophobic antifreeze composite powder generated by the mercapto-functionalized wind turbine blade powder and fluorinated acrylate through a mercapto-olefin click chemical reaction in step (4) is generated by fully diluting and dispersing the mercapto-functionalized wind turbine blade powder into a mixture B with a mass concentration of 1-10 wt%, diluting the fluorinated acrylate into a fluorinated acrylate solution with a mass concentration of 2-25 wt%, adding the fluorinated acrylate solution to the mixture B under stirring conditions, then adding an initiator, and stirring and reacting at a temperature of 60-80°C for 9-12 hours. After the time is up, the superhydrophobic antifreeze composite powder is obtained by filtration, washing and drying.
[0030] In the above technical solution, the initiator is an initiator commonly used in polymerization reactions in this technical field. Those skilled in the art can select a suitable initiator according to actual needs. For example, the initiator may include any one of azobisisobutyronitrile, triethylamine, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, and 4-dimethylaminopyridine; the amount of initiator added is 1-20% of the mass of the mercapto-functionalized wind turbine blade powder.
[0031] In this document, the solvent mentioned in step (5) is a solvent commonly used in chemical coating products, such as any one or more of anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate.
[0032] In one preferred embodiment, the superhydrophobic antifreeze coating further comprises, by weight parts:
[0033] 1-10 parts of filler
[0034] Additives: 1 to 10 parts.
[0035] In order to improve the physical strength of the coating film after the superhydrophobic antifreeze coating is applied, the raw material components include fillers, which are known and commonly used inorganic or organic fillers, preferably one or more of titanium dioxide, bentonite, barium sulfate, spherical silica, nano calcium carbonate, and talc. Further, it is preferred that known and commonly used metal oxides are used as both fillers and pigments.
[0036] The additive is one or more of pigments, thickeners, defoamers, leveling agents, antioxidants, and rust inhibitors. Typically, the pigments, thickeners, defoamers, leveling agents, antioxidants, and rust inhibitors mentioned above are commonly known and used.
[0037] It should be noted that the superhydrophobic antifreeze coating provided by this invention follows the conventional coating method for hydrophobic coatings in the chemical industry. For example, after applying a layer of adhesive to a smooth substrate, the superhydrophobic antifreeze coating is then applied to its surface, and after drying, a superhydrophobic antifreeze coating is obtained.
[0038] Typically, the coating method is one of spraying, brushing, or dipping; the adhesive includes, but is not limited to, 3M adhesive, commonly used coating resin adhesive, inorganic adhesive, etc.; the substrate is any one of textiles, glass, wood, stainless steel mesh, copper mesh, sponge, aluminum, iron, cement board, ceramics, or paper products.
[0039] The present invention has the following beneficial effects:
[0040] (1) This invention provides a method for preparing superhydrophobic antifreeze coatings using waste wind turbine blades. Based on the special properties of wind turbine blade powder obtained by grinding waste wind turbine blade material in an industrial disc-shaped solid-state chemical reactor, comparative experiments have shown that the powder after grinding in an industrial disc-shaped solid-state chemical reactor has significantly improved hydrophobic properties compared with powder obtained by other crushing / breaking methods under similar particle size conditions. The coating formed by preparing the coating has a rough surface and multi-scale structure. Moreover, this structural characteristic, combined with subsequent hydrophobic modification, improves the hydrophobicity and achieves efficient expression of the modification effect.
[0041] (2) This invention provides a method for preparing superhydrophobic antifreeze coatings using waste wind turbine blades. The method involves reacting thiol-functionalized wind turbine blade powder with fluorinated acrylate via thiol (thiol-alkene click chemistry) to generate a superhydrophobic antifreeze composite powder, which exhibits excellent hydrophobic properties. The coating prepared using this material has a hierarchical structure and low surface free energy, as well as good mechanical properties, durability, chemical stability and anti-icing properties. It also has excellent stain resistance and self-cleaning properties, thus expanding high-value application scenarios for the reuse of waste wind turbine blade materials.
[0042] (3) This invention provides a method for preparing superhydrophobic antifreeze coatings using waste wind turbine blades. The coating formed by applying the prepared coating has a multi-scale rough surface structure that reduces heat transfer, improves antifreeze capability, and increases the functional application of recycled materials. This not only challenges the traditional concept that mechanically recycled wind turbine blades can only be used as low-value fillers, but also demonstrates the huge potential for value-added recycling of glass fiber reinforced polymers. Attached Figure Description
[0043] Figure 1 SEM images of the wind turbine blade powder prepared in Example 1 of this invention are used to verify the present invention.
[0044] Figure 2Figure 3 shows the reaction process of steps (2) to (4) in Example 3 of this invention, as well as the FTIR spectrum, XPS spectrum, high-resolution carbon spectrum, SEM image, mapping image, and TG curve of the intermediate product. Specifically, Figure (a) is a schematic diagram of the reaction process of steps (2) to (4) in Example 3; Figure (b) shows the FTIR comparison spectra of the wind turbine blade powder (WGE) obtained in step (2), the thiol-functionalized wind turbine blade powder (WGE@KH590) obtained in step (3), and the superhydrophobic antifreeze composite powder (S@WGE@KH590) obtained in step (4) in Example 3; Figure (c) shows the wind turbine blade powder (WGE) obtained in step (2), the thiol-functionalized wind turbine blade powder (WGE@Kh) obtained in step (3), and the superhydrophobic antifreeze composite powder (S@WGE@Kh) obtained in step (4) in Example 3. Figure 1 shows the XPS comparison spectrum; Figure 2 shows the high-resolution carbon spectrum of the thiol-functionalized modified wind turbine blade powder obtained in step (3) of Example 3; Figure 3e shows the high-resolution carbon spectrum of the superhydrophobic antifreeze composite powder obtained in step (4) of Example 3; Figure 4f shows the SEM image and mapping image of the superhydrophobic antifreeze composite powder obtained in step (4) of Example 3; Figure 5g shows the TG curve comparison of the wind turbine blade powder (WGE) obtained in step (2), the thiol-functionalized modified wind turbine blade powder (WGE@Kh) obtained in step (3), and the superhydrophobic antifreeze composite powder (S@WGE@Kh) obtained in step (4) of Example 3.
[0045] Figure 3 This is an SEM image of the surface of the coated sample in Example 3 of the present invention. Detailed Implementation
[0046] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. Those skilled in the art can refer to the content of this document to appropriately improve the process parameters. In particular, it should be noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the scope of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate changes and combinations to the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. Although it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in the present invention.
[0047] In one aspect, the present invention provides a method for preparing superhydrophobic antifreeze coatings using discarded wind turbine blades, mainly comprising the following steps:
[0048] (1) After the waste wind turbine blade material has undergone pretreatment including washing, it is processed and crushed into wind turbine blade fragments with an average particle size of no more than 3 cm.
[0049] (2) The wind turbine blade fragments obtained in step (1) are added to a grinding disc-shaped solid-state chemical reactor for grinding and crushing. After grinding is completed, the wind turbine blade powder is collected. The process parameters of the grinding disc-shaped solid-state chemical reactor are: grinding pressure of 4-6 MPa, grinding disc surface temperature of 20-30℃ by introducing circulating cooling liquid, grinding at least once, and grinding disc speed of 20-40 rpm.
[0050] (3) The wind turbine blade powder obtained in step (2) is modified by a silane coupling agent containing thiol to prepare thiol-functionalized wind turbine blade powder.
[0051] (4) The thiol-functionalized modified wind turbine blade powder obtained in step (3) is reacted with fluorinated acrylate through a thiol-olefin click chemical reaction to generate a superhydrophobic antifreeze composite powder.
[0052] The fluorinated acrylate has at least one fluorine atom and a carbon chain length of 4 to 20.
[0053] (5) Using the superhydrophobic antifreeze composite powder obtained in step (4) as a raw material, mix it evenly with the other raw materials listed below to prepare a superhydrophobic antifreeze coating:
[0054] 3-5 parts of superhydrophobic antifreeze composite powder
[0055] Solvent 90-95 parts.
[0056] In this article, step (1) includes a pretreatment of washing, which mainly removes impurities from the surface of the waste wind turbine blade material. If necessary, the non-wind turbine blade material should also be removed. Those skilled in the art can carry out specific treatment according to the actual condition of the waste wind turbine blade products that they need to recycle, based on existing technologies.
[0057] In this article, the wind turbine blade fragments processed and crushed to a uniform particle size of no more than 3 cm in step (1) can be processed and crushed using conventional crushing methods, such as jaw crushers, planetary ball mills, cryogenic ball mills, and other existing conventional crushing equipment, in order to facilitate their placement into a disc-shaped solid-phase mechanical chemical reactor for grinding.
[0058] The millstone-shaped solid-phase mechanochemical reactor mentioned in step (2) is the industrial millstone-shaped solid-phase mechanochemical reactor disclosed in Chinese invention patent CN114534660B.
[0059] It should be noted that this industrial millstone-shaped solid-phase mechanochemical reactor is an industrial device that is an improvement on the mechanochemical reactor disclosed in the prior authorized patent ZL95111258.9. It is significantly different from the structure of the laboratory prototype machine when ZL95111258.9 was applied for. It has designed a brand-new millstone structure for industrial high-efficiency mechanochemical grinding, which has been improved from the previous vertical millstone setting to a horizontal setting, and the size of the millstone has been greatly increased. Based on the horizontal setting and large size of the millstone, related fixed millstone components and hydraulic lifting system have been innovatively designed, which greatly improves its three-dimensional shear force, thereby achieving industrial mass production efficiency.
[0060] Typically, the grinding process is at least once. When the grinding process is twice or more, the actual operation involves grinding the material in a disc-shaped solid-state chemical reactor, collecting the product at the discharge end, and then placing it back into the disc-shaped solid-state chemical reactor for grinding. This process is considered as two grinding cycles.
[0061] In this article, the grinding disc surface temperature in step (2) is controlled to be 20-30°C by introducing a circulating cooling liquid, which is water, ethylene glycol or glycerin.
[0062] In this document, the thiol-containing silane coupling agent mentioned in step (3) is a commercially available silane coupling agent with a thiol functional group commonly used in the prior art. In one embodiment, for example, one or more of KH590 and KH580 may be selected.
[0063] In this paper, the wind turbine blade powder described in step (3) is modified with a thiol-containing silane coupling agent to obtain thiol-functionalized wind turbine blade powder. Modifying the material using a thiol-containing silane coupling agent is a conventional modification method in the art, and the specific modification conditions and operations can be referred to the instructions for use of the selected silane coupling agent or existing technical literature. In one embodiment, during the modification process, the thiol-containing silane coupling agent needs to be diluted to a coupling agent solution with a mass concentration of 1-3 wt%, and then added to the wind turbine blade powder for reaction; or the wind turbine blade powder is fully diluted and dispersed in a mixture A with a mass concentration of 1-3 wt%, and then the thiol-containing silane coupling agent is added for reaction. The dilution and the solvent used for dilution are conventional and well-known methods for using silane coupling agents. Those skilled in the art can directly select a suitable method based on common knowledge in the art or the instructions for use of the thiol-containing silane coupling agent.
[0064] To better illustrate the present invention and provide a reference embodiment, the wind turbine blade powder described in step (3) is modified with a thiol-containing silane coupling agent to obtain thiol-functionalized wind turbine blade powder. The specific method is as follows:
[0065] By mass, 1-2 parts of wind turbine blade powder are added to 90-99 parts of ethanol and 1-3 parts of deionized water, and the mixture is continuously stirred for 30-40 minutes to disperse it. Then, 1-5 parts of silane coupling agent containing mercapto groups are added, and the mixture is stirred and reacted at a temperature of 90-100℃ for 8-16 hours. After the time is up, the mixture is filtered, washed, and dried to obtain mercapto-functionalized modified wind turbine blade powder.
[0066] In one embodiment, the fluorinated acrylate in step (4) is selected from 1H,1H,2H,2H-perfluorodecyl acrylate, trifluoroethyl acrylate, N-ethylperfluorooctylsulfonamide ethyl acrylate, 1,1,2,2-tetrahydroperfluorohexyl methacrylate, 1,1,2,2-tetrahydroperfluorodecyl methacrylate, 1,1,2,2-tetrahydroperfluorooctyl methacrylate, 1,1,2,2-tetrahydroperfluorododecyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 3-( The following are all of the following: perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 1H,1H,2H,2H-perfluorooctyl acrylate, 1,1,2,2-tetrahydroperfluorotetradecyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, perfluoroalkyl ethyl methacrylate, perfluoroalkyl ethyl acrylate, nonafluorohexadecyl acrylate, (2H-perfluoropropyl)-2-acrylate, and (perfluorocyclohexyl) methacrylate.
[0067] In this paper, the thiol-functionalized modified wind turbine blade powder and fluorinated acrylate in step (4) are reacted with thiol-olefin click chemistry to generate superhydrophobic antifreeze composite powder. Those skilled in the art can know the reaction conditions and process operation of thiol (thiol-olefin click chemistry) reaction based on the common knowledge of chemical synthesis in the art, according to the selection of thiol-functionalized modified wind turbine blade powder and fluorinated acrylate provided by this invention. For example, the initiator, solvent and target product used can all refer to conventional thiol (thiol-olefin click chemistry) reaction.
[0068] To better illustrate the present invention and provide a reference embodiment, the superhydrophobic antifreeze composite powder generated by the mercapto-functionalized wind turbine blade powder and fluorinated acrylate through a mercapto-olefin click chemical reaction in step (4) is generated by fully diluting and dispersing the mercapto-functionalized wind turbine blade powder into a mixture B with a mass concentration of 1-10 wt%, diluting the fluorinated acrylate into a fluorinated acrylate solution with a mass concentration of 2-25 wt%, adding the fluorinated acrylate solution to the mixture B under stirring conditions, then adding an initiator, and stirring and reacting at a temperature of 60-80°C for 9-12 hours. After the time is up, the superhydrophobic antifreeze composite powder is obtained by filtration, washing and drying.
[0069] In the above embodiments, the initiator is an initiator commonly used in polymerization reactions in this technical field. Those skilled in the art can select a suitable initiator according to actual needs. For example, the initiator selection includes any one of azobisisobutyronitrile, triethylamine, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, and 4-dimethylaminopyridine; the amount of initiator added is 1-20% of the mass of the mercapto-functionalized wind turbine blade powder, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any range or point value between them.
[0070] In this document, the solvent mentioned in step (5) is a solvent commonly used in chemical coating products, and in one embodiment, it is any one or more of anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate.
[0071] In one preferred embodiment, the superhydrophobic antifreeze coating further comprises, by weight parts:
[0072] 1-10 parts of filler
[0073] Additives: 1 to 10 parts.
[0074] In order to improve the physical strength of the coating film after the superhydrophobic antifreeze coating is applied, the raw material components include fillers, which are known and commonly used inorganic or organic fillers, preferably one or more of titanium dioxide, bentonite, barium sulfate, spherical silica, nano calcium carbonate, and talc. Further, it is preferred that known and commonly used metal oxides are used as both fillers and pigments.
[0075] The additive is one or more of pigments, thickeners, defoamers, leveling agents, antioxidants, and rust inhibitors. Typically, the pigments, thickeners, defoamers, leveling agents, antioxidants, and rust inhibitors mentioned above are commonly known and used.
[0076] It should be noted that the superhydrophobic antifreeze coating provided by this invention follows the conventional coating method for hydrophobic coatings in the chemical industry. For example, after applying a layer of adhesive to a smooth substrate, the superhydrophobic antifreeze coating is then applied to its surface, and after drying, a superhydrophobic antifreeze coating is obtained.
[0077] Typically, the coating method is one of spraying, brushing, or dipping; the adhesive includes, but is not limited to, 3M adhesive, commonly used coating resin adhesive, inorganic adhesive, etc.; the substrate is any one of textiles, glass, wood, stainless steel mesh, copper mesh, sponge, aluminum, iron, cement board, ceramics, or paper products.
[0078] The present application will be further explained in detail below with reference to embodiments. However, those skilled in the art should understand that these embodiments are provided for illustrative purposes only and are not intended to limit the present application.
[0079] Example
[0080] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of this application. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all commercially available conventional products. This application should not be construed as being limited to the specific embodiments described.
[0081] 1. Raw materials
[0082] Waste wind turbine blades, provided by Tianjin Longjin Energy Saving Technology Co., Ltd.
[0083] Epoxy resin (EP-128), Chengdu Kemete Technology Co., Ltd.
[0084] 1H,1H,2H,2H-Perfluorodecyl acrylate, 2,2′-Azobis(2-methylpropionitrile) (AIBN), 4,4′-Diaminodiphenylmethane (DDM), (3-mercaptopropyl)trimethoxysilane (KH-590), Tetrahydrofuran (THF, anhydrous), Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0085] Ethanol (EtOH, AR), acetone (99.5%), hydrochloric acid (HCl, 36-38%), sodium hydroxide (NaOH, 96%) and deionized water, Chengdu Kelong Reagent Factory.
[0086] 2. Preparation method
[0087] (1) After undergoing pretreatment including washing, the waste wind turbine blade material is crushed into wind turbine blade fragments by a crusher.
[0088] (2) The wind turbine blade fragments obtained in step (1) are added to a grinding disc-shaped solid-state mechanical chemical reactor for grinding and crushing. After grinding is completed, the wind turbine blade powder is collected. The process parameters of the grinding disc-shaped solid-state mechanical chemical reactor are: grinding pressure of 5 MPa, grinding disc surface temperature of 20°C by introducing circulating cooling liquid, grinding at least once, and grinding disc speed of 40 rpm.
[0089] (3) By mass fraction, add 2 parts of wind turbine blade powder obtained in step (2) to 96 parts of ethanol and 2 parts of deionized water, stir continuously for 30 minutes to disperse, then add 2 parts of KH590, stir and react at 100℃ for 12 hours, and after the time is up, filter, wash and dry to obtain mercapto-functionalized modified wind turbine blade powder.
[0090] (4) By mass fraction, 5 parts of the mercapto-functionalized modified wind turbine blade powder obtained in step (3) are dispersed in 80 parts of THF as mixture B. 5 parts of 1H,1H,2H,2H-perfluorodecyl acrylate are dissolved in 40 parts of THF as fluorinated acrylate solution. The fluorinated acrylate solution is added to mixture B under stirring. Then, 1 part of initiator AIBN is added. The mixture is stirred and reacted at 80°C for 12 hours. After the time is up, the mixture is filtered, washed and dried to obtain superhydrophobic antifreeze composite powder.
[0091] (5) Using the superhydrophobic antifreeze composite powder obtained in step (4) as a raw material, mix it evenly with the other raw materials listed below to prepare a superhydrophobic antifreeze coating:
[0092] Three parts of superhydrophobic antifreeze composite powder
[0093] 95 parts of ethanol.
[0094] For ease of testing, all glass substrates were ultrasonically cleaned with ethanol and dried at 60°C before use. First, 8 parts by weight of commercially available epoxy resin, 1 part DDM, and 90 parts by weight of acetone were mixed under stirring. The mixture was then sprayed onto a glass slide and pre-cured at 60°C for 30 minutes as the substrate. Next, a superhydrophobic antifreeze coating was sprayed onto the substrate surface using a spray gun. Finally, the coating was cured at 60°C for 8 hours to obtain the coating sample. The air pressure used for spraying was 30 psi.
[0095] 3. Testing Methods
[0096] Fourier transform infrared spectroscopy (FTIR) test
[0097] Transmission mode spectral analysis of the samples was performed using a Nicolet 6700 Fourier transform infrared spectrometer from Thermo Fisher Scientific, USA. The spectrometer scanning range was 4000-400 cm⁻¹. -1 The resolution is 4cm. -1 The scan was performed 32 times. The transmission mode used KBr pellet compression.
[0098] X-ray photoelectron spectroscopy (XPS) test
[0099] Elemental composition and composition of samples were analyzed using an AXIS Ultra DLD X-ray photoelectron spectrometer from Kratos Analytical Instruments, UK, using a monochromatic Al Kα X-ray source (40 kV, 40 mA) at room temperature. All binding energies were calibrated to the C1s hydrocarbon peak at 284.8 eV. All samples were dried in a vacuum oven at 65 °C for 24 hours prior to testing. Energy dispersive spectral data and spectra of C, N, O, P, and Si were recorded.
[0100] Scanning electron microscopy (SEM) analysis
[0101] The surface morphology of all samples was observed using an Inspect F scanning electron microscope from FEI Corporation, USA. Test conditions: accelerating voltage 20 kV; samples underwent gold sputtering treatment before testing. Elemental spectra were obtained using energy-dispersive X-ray spectroscopy (EDS) elemental analysis mounted on the scanning electron microscope.
[0102] Static contact angle test
[0103] Contact angle tests were conducted under environmental conditions using a Krüss DSA25 optical contact angle analyzer (Hamburg, Germany).
[0104] Thermogravimetric analysis (TGA)
[0105] The change in mass of samples with temperature in an N2 atmosphere was tested using a Q50 thermogravimetric analyzer from TA Instruments, USA. Heating rate: 10℃ / min; Temperature range: 40-800℃.
[0106] Anti-icing test observation
[0107] The anti-icing properties of the material were tested using a self-made low-temperature testing apparatus. All experiments were conducted at a humidity of approximately 80 ± 5% RH. The freezing process of the droplets was then recorded using a camera.
[0108] Roughness test
[0109] The surface morphology and roughness of the coating were measured using a laser confocal microscope (LSM 700).
[0110] Verification Example 1
[0111] Verification Example 1 is prepared by following the steps (1), (2), and (5) of "2. Preparation Method" above, that is, by directly using the wind turbine blade powder obtained in step (2) as a raw material to mix with ethanol to prepare a hydrophobic coating.
[0112] In step (2), the grinding is performed once, and a hydrophobic coating is finally prepared. The coating film sample is then tested.
[0113] First, the effects of different pulverization methods on the hydrophobicity of the final coating were compared, as shown in Table 1 below:
[0114] Table 1. Effect of different pulverization methods on hydrophobicity
[0115] Jaw crusher 240 31.45 79.8 Planetary ball mill 150 31.12 80.1 Refrigerated ball mill 120 30.15 82.3 Verification Example 1 5 30.51 86.3
[0116] Table 1 shows implementation schemes based on Verification Example 1, with the only difference being that the disc-shaped solid-phase mechanochemical reactor was replaced with other conventional pulverizing equipment. The resulting wind turbine blade powders all passed through a 500-mesh sieve. It is evident that, under similar particle size conditions, Verification Example 1 exhibits a significant improvement in hydrophobic properties.
[0117] Verification Examples 2-5
[0118] Verification Examples 2 to 5 are based on Verification Example 1, wherein the number of milling times in step (2) is 2, 3, 5 and 10 times respectively, and finally a hydrophobic coating is prepared and its coating sample is tested.
[0119] Secondly, the effects of different milling times on the hydrophobicity of the final coating were compared, as shown in Table 2 below:
[0120] Table 2. Effect of different milling times on hydrophobicity
[0121] 0 1935 68.6 Verification Example 1 1 30.68 86.4 Verification Example 2 2 21.08 88.2 Verification Example 3 3 19.19 88.7 Verification Example 4 5 19.17 88.9 Verification Example 5 10 18.58 89.1
[0122] In Table 2, the number of milling cycles is 0, which is based on the implementation scheme of Verification Example 1, without performing step (2), that is, using the wind turbine blade fragments obtained in step (1) as raw materials to perform step (5). It can be clearly seen that as the number of milling cycles increases, the particle size of the wind turbine blade powder shows a decreasing trend, but the trend of its hydrophobicity enhancement is not obvious. Based on comprehensive consideration, the number of milling cycles is preferably 2 to 3 times.
[0123] Example 1
[0124] Example 1 is prepared according to the above "2. Preparation method", wherein the number of milling times in step (2) is 1, and the superhydrophobic antifreeze coating is finally prepared and its coating sample is tested.
[0125] Example 2
[0126] Example 2 is prepared according to the above "2. Preparation method", wherein the number of milling times in step (2) is 2 times, and the superhydrophobic antifreeze coating is finally prepared and its coating sample is tested.
[0127] Example 3
[0128] Example 3 is prepared according to the above "2. Preparation method", wherein the number of milling times in step (2) is 3 times, and the superhydrophobic antifreeze coating is finally prepared and its coating sample is tested.
[0129] Example 4
[0130] Example 4 is prepared according to the above "2. Preparation method", wherein the number of milling times in step (2) is 5 times, and the superhydrophobic antifreeze coating is finally prepared and its coating sample is tested.
[0131] Example 5
[0132] Example 5 is prepared according to the above "2. Preparation method", wherein the number of milling times in step (2) is 10 times, and the superhydrophobic antifreeze coating is finally prepared and its coating sample is tested.
[0133] Based on the coating sample obtained in Example 3, paper was used for cyclic rubbing. After the experiment, its water contact angle was measured. A normal force of 1N was applied to the rubbing paper, and the number of rubbing cycles was 20, 60, 100, 140, 180, 220, 260, and 300. The effect of different rubbing cycles on the hydrophobic stability of the coating sample is detailed in Table 3.
[0134] Table 3. Effect of different milling times on hydrophobic stability
[0135] 20 162.1 60 160.1 100 158.1 140 160.4 180 155.0 220 154.4 260 149.5 300 147.2
[0136] Based on the coating sample obtained in Example 3, it was immersed in 1 mol / L HCl solution for a specified time. After the experiment, its water contact angle was measured. The specified immersion times were 8, 16, 24, 32, 40, and 48 hours. The effect of different immersion times on the hydrophobicity of the coating sample is detailed in Table 4.
[0137] Table 4. Effect of different immersion times in acid solution on the hydrophobicity of the coated samples.
[0138] 8 161.0 16 162.3 24 158.4 32 157.2 40 159.3 48 156.4
[0139] Based on the coating sample obtained in Example 3, it was immersed in 1 mol / L NaCl solution for a specified time. After the experiment, its water contact angle was measured. The specified immersion times were 8, 16, 24, 32, 40, and 48 hours. The effect of different immersion times on the hydrophobicity of the coating sample is detailed in Table 5.
[0140] Table 5. Effect of different immersion times in salt solution on the hydrophobicity of the coated samples.
[0141] 8 161.1 16 158.3 24 158.5 32 158.4 40 156.8 48 152.6
[0142] Based on the coating sample obtained in Example 3, it was immersed in 1 mol / L NaOH solution for a specified time. After the experiment, its water contact angle was measured. The specified immersion times were 4, 8, 12, 16, 20, and 24 hours. The effect of different immersion times on the hydrophobicity of the coating sample is detailed in Table 6.
[0143] Table 6. Effect of different immersion times in alkaline solution on the hydrophobicity of the coated samples.
[0144] 4 158.4 8 155.3 12 153.3 16 150.1 20 145.5 24 132.6
[0145] Based on the coating sample obtained in Example 3, water flow impact was applied, and the water contact angle was measured after the experiment. The impact angle was 45°, the water flow velocity was 10 g / s, the water flow height was 15 cm, and the impact time was 5–30 minutes. The effect of water flow impact time on the hydrophobicity of the coating sample is detailed in Table 7.
[0146] Table 7. Effect of different water flow impact times on the hydrophobicity of the coating samples.
[0147] 5 160.1 10 157.1 15 159.7 20 157.2 25 158.2 30 156.2
[0148] Based on the coating samples obtained in Example 3, their antifreeze ability was tested in a freezer, and their ice coverage was observed. The temperature was set at -15℃, and the freezing time was 0–6 hours. The effect of freezing time on the dynamic antifreeze performance of the coating samples is detailed in Table 8.
[0149] Table 8. Effects of different freezing times on the dynamic antifreeze performance of the coated samples.
[0150] 0.5 0 1 0 2 15 3 28 4 49 5 65 6 79
[0151] Comparative Example 1
[0152] Comparative Example 1 was prepared by mixing 8 parts by weight of commercially available epoxy resin, 1 part of DDM, and 90 parts by weight of acetone under stirring conditions. The mixture was then sprayed onto a glass slide and pre-cured at 60°C for 30 minutes to serve as a control sample. The air pressure used for spraying was 30 psi.
[0153] Comparative Example 2
[0154] Comparative Example 2 involved mixing 8 parts by weight of commercially available epoxy resin, 1 part of DDM, and 90 parts of acetone under stirring conditions. The mixture was then sprayed onto a glass slide and pre-cured at 60°C for 30 minutes as a substrate. Next, 3 parts of 1H,1H,2H,2H-perfluorodecyl acrylate and 95 parts of ethanol were mixed as a coating and sprayed onto the substrate surface using a spray gun. Finally, the coating was cured at 60°C for 8 hours to obtain a comparative sample. The air pressure used for spraying was 30 psi.
[0155] Water contact angle tests were performed on the samples obtained from Example 3, Verification Example 3, Comparative Example 1, and Comparative Example 2. A comparison of the hydrophobicity of different hydrophobic coatings is detailed in Table 9.
[0156] Table 9 Comparison of hydrophobicity of different hydrophobic coatings
[0157] Comparative Example 1 EP 92.4 Verification Example 3 EP / WGE 89.1 Comparative Example 2 EP / PFTDA 119.3 Example 3 EP / S@WGE@Kh 162.0
[0158] The samples obtained in Verification Example 3 and Comparative Example 1 were tested for their antifreeze capabilities. The temperature was set to -15°C, and the freezing times were 0.5 and 1 hour, respectively. A comparison of the dynamic antifreeze performance of different hydrophobic coatings is detailed in Table 10.
[0159] Table 10 Comparison of dynamic antifreeze performance of different hydrophobic coatings
[0160]
[0161] Based on the coating sample obtained in Example 3, the contact angles were measured after contacting milk, tea, coffee, orange juice, and cola, respectively. The effects of different liquid environments on the hydrophobicity of the coating sample are detailed in Table 11.
[0162] Table 11 Effects of different liquid environments on the hydrophobicity of the coating samples
[0163] milk 158.0 Tea 160.0 coffee 157.0 Orange juice 159.0 Cola 156.0
[0164] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing superhydrophobic antifreeze coatings using discarded wind turbine blades, characterized in that... Includes the following steps: (1) After the waste wind turbine blade material has undergone pretreatment including washing, it is processed and crushed into wind turbine blade fragments with an average particle size of no more than 3 cm. (2) The wind turbine blade fragments obtained in step (1) are added to a grinding disc-shaped solid-state mechanical chemical reactor for grinding and crushing. After grinding is completed, the wind turbine blade powder is collected. The process parameters of the grinding disc-shaped solid-state mechanical chemical reactor are: grinding pressure of 4~6MPa, grinding disc surface temperature controlled by circulating cooling liquid at 20~30℃, grinding at least once, and grinding disc speed of 20~40 rpm. (3) The wind turbine blade powder obtained in step (2) is modified with a silane coupling agent containing thiol to prepare thiol-functionalized wind turbine blade powder; (4) The thiol-functionalized modified wind turbine blade powder obtained in step (3) is reacted with fluorinated acrylate through a thiol-olefin click chemical reaction to generate a superhydrophobic antifreeze composite powder. The fluorinated acrylate has at least one fluorine atom and a carbon chain length of 4 to 20. (5) Based on the mass fraction, the superhydrophobic antifreeze composite powder obtained in step (4) is used as a raw material and mixed evenly with other raw materials including the following to prepare a superhydrophobic antifreeze coating: 3-5 parts of superhydrophobic antifreeze composite powder Solvent 90-95 parts.
2. The method according to claim 1, characterized in that: The thiol-containing silane coupling agent mentioned in step (3) includes any one or more of KH590 and KH580.
3. The method according to claim 1, characterized in that: The wind turbine blade powder described in step (3) is modified with a thiol-containing silane coupling agent to obtain thiol-functionalized wind turbine blade powder. The specific method is as follows: By mass, 1-2 parts of wind turbine blade powder are added to 90-99 parts of ethanol and 1-3 parts of deionized water, and the mixture is continuously stirred for 30-40 minutes to disperse it. Then, 1-5 parts of silane coupling agent containing mercapto groups are added, and the mixture is stirred and reacted at 90-100℃ for 8-16 hours. After the reaction time is reached, the mixture is filtered, washed, and dried to obtain mercapto functionalized modified wind turbine blade powder.
4. The method according to claim 1, characterized in that: The fluorinated acrylates mentioned in step (4) include 1H,1H,2H,2H-perfluorodecyl acrylate, trifluoroethyl acrylate, N-ethylperfluorooctylsulfonamide ethyl acrylate, 1,1,2,2-tetrahydroperfluorohexyl methacrylate, 1,1,2,2-tetrahydroperfluorodecyl methacrylate, 1,1,2,2-tetrahydroperfluorooctyl methacrylate, 1,1,2,2-tetrahydroperfluorododecyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, and 3-(perfluoro-5-methyl) The following are all of the following: (hexyl)-2-hydroxypropyl methacrylate, 1H,1H,2H,2H-perfluorooctyl acrylate, 1,1,2,2-tetrahydroperfluorotetradecyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, perfluoroalkyl ethyl methacrylate, perfluoroalkyl ethyl acrylate, nonafluorohexadecyl acrylate, (2H-perfluoropropyl)-2-acrylate, and (perfluorocyclohexyl) methacrylate.
5. The method according to claim 1, characterized in that: The superhydrophobic antifreeze composite powder is generated by the mercapto-functionalized wind turbine blade powder and fluorinated acrylate through a thiol-olefin click chemical reaction in step (4). The mercapto-functionalized wind turbine blade powder is fully diluted and dispersed into a mixture B with a mass concentration of 1-10 wt%. The fluorinated acrylate is diluted to a fluorinated acrylate solution with a mass concentration of 2-25 wt%. The fluorinated acrylate solution is added to the mixture B under stirring conditions. Then an initiator is added, and the mixture is stirred and reacted at a temperature of 60-80℃ for 9-12 hours. After the time is up, the superhydrophobic antifreeze composite powder is obtained by filtration, washing and drying.
6. The method according to claim 5, characterized in that: The initiator includes azobisisobutyronitrile; the amount of the initiator added is 1-20% of the mass of the mercapto-functionalized wind turbine blade powder.
7. The method according to claim 1, characterized in that: The solvent mentioned in step (5) includes any one or more of the following: anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate.
8. The method according to claim 1, characterized in that: Its raw materials, by mass parts, also include: 1-10 parts of filler Additives: 1-10 parts.
9. The method according to claim 1, characterized in that: The number of grinding cycles in step (2) is 2 to 3.
10. The superhydrophobic antifreeze coating prepared by the method for preparing superhydrophobic antifreeze coating using waste wind turbine blades as described in claim 1.
Citation Information
Patent Citations
Mechanico-chemical reactor
CN1130545A
An industrial millstone-shaped solid-phase mechanochemical reactor
CN114534660B
Multifunctional super-amphiphobic fabric and preparation method thereof and application thereof
CN109610161A
Glass fiber reinforced plastic regenerated product using waste wind turbine blade as raw material and preparation method of glass fiber reinforced plastic regenerated product
CN118063854A